Microbial consumption of zero-valence sulfur in marine benthic habitats - Pjevac, Petra; Kamyshny Jr., Alexey; Dyksma, Stefan; Mussmann, Marc (ENVIRONMENTAL MICROBIOLOGY, 2014)
Zero-valence sulfur (S-0) is a central intermediate in the marine sulfur cycle and forms conspicuous accumulations at sediment surfaces, hydrothermal vents and in oxygen minimum zones. Diverse microorganisms can utilize S-0, but those consuming S-0 in the environment are largely unknown. We identified possible key players in S-0 turnover on native or introduced S-0 in benthic coastal and deep-sea habitats using the 16S ribosomal RNA approach, (in situ) growth experiments and activity measurements. In all habitats, the epsilonproteobacterial Sulfurimonas/Sulfurovum group accounted for a substantial fraction of the microbial community. Deltaproteobacterial Desulfobulbaceae and Desulfuromonadales were also frequently detected, indicating S-0 disproportionation and S-0 respiration under anoxic conditions. Sulfate production from S-0 particles colonized in situ with Sulfurimonas/Sulfurovum suggested that this group oxidized S-0. We also show that the type strain Sulfurimonas denitrificans is able to access cyclooctasulfur (S-8), a metabolic feature not yet demonstrated for sulfur oxidizers. The ability to oxidize S-0, in particular S-8, likely facilitates niche partitioning among sulfur oxidizers in habitats with intense microbial sulfur cycling such as sulfidic sediment surfaces. Our results underscore the previously overlooked but central role of Sulfurimonas/Sulfurovum group for conversion of free S-0 at the seafloor surface.
Keywords: HOV Alvin (Human Occupied Vehicle)